Core-section summary for IODP Site 386-M0088 - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
List of recovered core sections from the above given site of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. Cores have been acquired by the use of a Giant Piston Coring (GPC) System. Recovered cores were divided into approx. 1 m long sections that are numbered sequentially from the top, starting at 1. Following IODP convention, material recovered from the core catcher of a sedimentary core is treated as a separate section labelled CC for core catcher and placed below the last section recovered from the core barrel. Most core catcher sections were placed in a bag due to their consistency. The IODP standard naming of sections includes the following information: expedition number, hole, core, core type and section. For example, a section label (column "Sample label") "386-M0081D-1H-12" represents section 12, core 1H ("H" [for hydraulic piston corer] indicates GPC cores, and "P" [for push corer] indicates trigger corer cores; see core summaries of this expedition), from Hole M0081D during Expedition 386. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023